POLAROGRAPHIC DETERMINATION AND ANTIFUNGAL ACTIVITY OF CU (II) COMPLEX WITH 3-HYDROXY-3-M-TOLYL-1-P-(SULPHONAMIDO) PHENYLTRIAZENE (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
The electrochemical behavior of complex of Cu (II) with 3-hydroxy-3-m-tolyl-1-p-(sulphonamido) phenyltriazene was studied. It was observed that HTSP forms 1:3 complex with Cu (II) in between pH 6.5 to 7.1. It was found that the reduction process of Cu (II) - HTSP complex is two electrons reversible reduction process at D.M.E. The logarithm value of stability constant of 1:3 Cu(II)-3-hydroxy-3-m-tolyl-1-p-(Sulphonamido) phenyltriazene complex has been found to be 11.63. The present paper also reports antifungal activity of hydroxytriazene 3-hydroxy-3-m-tolyl-1-(4-sulphonamidophenyl) triazene, and its Cu (II) complex against Rhizoctonia solani, the fungi causing disease in fennel. The result has been expressed as percentage inhibition (PI) of mycelial growth as well as sclerotium formation at 500 ppm for both ligand as well as complex. The result shows that PI value in complex is 87.03 whereas for ligand 79.63. Thus it is clear that complex is better in activity against the fungi compared to its respective ligand. The result has been interpreted in terms of theory of drug action proposed by Paton.